The interplay of financial education, financial literacy, financial inclusion and financial stability: Any lessons for the current big tech era? - Nicole Jonker; Anneke Kosse (Bank of Canada, 2020)
The entry of Big Tech firms in the financial ecosystem might affect financial stability through the opportunities and challenges they create for financial inclusion. In this paper we survey the literature to determine the effectiveness of financial education in improving financial literacy and financial inclusion and to assess the impact of financial inclusion on financial stability. Based on our findings, we argue that new empirical research is needed to determine whether financial education can play a role in ensuring that everyone is able to reap the financial-inclusion benefits that Big Tech may bring. We also conclude that financial-inclusion opportunities created by Big Tech might potentially introduce risks for overall financial stability. Because of this, we underline the importance of proper supervision and regulation.
Keywords: D14; D91; D92; G21; G23; O16; 330; Development economics; Digital currencies and fintech; Financial markets; Financial services; Financial stability